3D printing for continuous fiber reinforced thermoplastic composites: mechanism and performance - Yang, Chuncheng; Tian, Xiaoyong; Liu, Tengfei; Cao, Yi; Li, Dichen (Rapid prototyping journal, 2017)
Purpose Continuous fiber reinforced thermoplastic composites (CFRTPCs) are becoming more significant in industrial applications but are limited by the high cost of molds, the manufacturing boundedness of complex constructions and the inability of special fiber alignment. The purpose of this paper is to put forward a novel three-dimensional (3D) printing process for CFRTPCs to realize the low-cost rapid fabrication of complicated composite components. Design/methodology/approach For this purpose, the mechanism of the proposed process, which consists of the thermoplastic polymer melting, the continuous fiber hot-dipping and the impregnated composites extruding, was investigated. A 3D printing equipment for CFRTPCs with a novel composite extrusion head was developed, and some composite samples have been fabricated for several mechanical tests. Moreover, the interface performance was clarified with scanning electron microscopy images. Findings The results showed that the flexural strength and the tensile strength of these 10 Wt.% continuous carbon fiber (CCF)/acrylonitrile-butadiene-styrene (ABS) specimens were improved to 127 and 147 MPa, respectively, far greater than the one of ABS parts and close to the one of CCF/ABS (injection molding) with the same fiber content. Moreover, these test results also exposed the very low interlaminar shear strength (only 2.81 MPa) and the inferior interface performance. These results were explained by the weak meso/micro/nano scale interfaces in the 3D printed composite parts. Originality/value The 3D printing process for CFRTPCs with its controlled capabilities for the orientation and distribution of fiber has great potential for manufacturing of load-bearing composite parts in the industrial circle.